Trickle-Down Effects of Positive and Negative Supervisor Behaviors on Service Performance: The Roles of Employee Emotional Labor and Perceived Supervisor Power. Issue 1 (1st January 2018) - Chi, Nai-Wen; Chen, Yen-Chun; Huang, Tun-Chun; Chen, Shih-Feng
ABSTRACT: Based on the trickle-down model, the present study simultaneously examined how transformational leadership and abusive supervision influence employees' proactive customer service performance and service sabotage through employees' emotional labor strategies toward customers. Moreover, this study examines whether perceived supervisor power can activate or inhibit the aforementioned trickle-down processes. The present study collected data from 186 service employees–supervisor pairs at different times. The results of structural equation modeling indicate that transformational leadership positively predicted employees' proactive customer service performance via deep acting, whereas abusive supervision was positively associated with employees' service sabotage through surface acting. Furthermore, being perceived as a powerful supervisor is an important factor to maximize the benefits of transformational leadership. The theoretical and practical implications are further discussed.